A Note on a Characterization of Gompertz-Verhulst Distribution - M. Ahsanullah; M. Shakil; B.M. Golam Kibria (Journal of Statistical Theory and Applications (JSTA), 2014)
Characterization of a probability distribution plays an important role in probability and statistics. This paper considers a new characterization of Gompertz-Verhulst distribution. It is hoped that the findings of the paper will be useful for researchers in different fields of applied sciences.